Of False Hair, Spanish Wool, and Witchcraft: The Act of Parliament That Never Was. (14th July 2022) - Daniell, Alison
Abstract: The wording of the so‐called Hoops and Heels Act of 1770 ostensibly permitted the husbands of women who had used beauty aids to 'betray [them] into matrimony' to declare their marriages null and void, and for those wives to be punished as witches. A set form of words, this supposed Act of Parliament has been quoted and re‐quoted across the globe since the late eighteenth century, even though its provisions never existed in law. This article analyses some of the Hoops and Heels text's possible cultural origins: namely eighteenth‐century understandings of witchcraft, the moral panic surrounding divorce and adultery, satires surrounding cosmetic usage as well as long‐standing discourses that – even today – associate women's sexual power over men with witchcraft and deception.